Hardware in the loop simulative setup for testing the combined heat power generating wind turbine - Ihor Shchur; Vsevolod Shchur; Ihor Bilyakovskyy; Mykhailo Khai (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
This paper describes the design and implementation of hardware in the loop (HIL) system based on induction motor wind turbine emulator for the study of the operation of a combined heat-power (CHP) generating wind energy conversion system (WECS). The energy generation part of the WECS consists of two specially designed generators that are placed on a common vertical axis, which is connected to the induction motor through a gearbox. The first generator is an electric two-armature axial PMSG and the second one is a thermal electromagnetic retarder. The software part of the HIL setup simulates the interaction of the wind flow with a vertical axis wind turbine (VAWT) and is implemented in a programmable logic controller based on the model developed in the MATLAB/Simulink. The results of experimental studies of the CHP WECS with the created HIL simulative setup at both constant and turbulent wind speeds have shown good agreement with the corresponding results of computer simulation. The created HIL simulative setup will be used for the development of an energy management system for CHP WECS.